Geomorphology of the Jebel Qara and coastal plain of Salalah (Dhofar, southern Sultanate of Oman). Issue 2 (9th December 2020) - Zerboni, Andrea; Perego, Alessandro; Mariani, Guido S.; Brandolini, Filippo; Al Kindi, Mohammed; Regattieri, Eleonora; Zanchetta, Giovanni; Borgi, Federico; Charpentier, Vincent; Cremaschi, Mauro
ABSTRACT: We present the results of the geomorphological mapping of a region of the Dhofar (Sultanate of Oman) including two contrasting physiographic units sharing a common drainage system into the Arabian Sea: the Jebel Qara limestone massif and the coastal plain of Salalah. Neogene to Quaternary tectonic activity controlled the formation of an extensive system of faults and caused the uplift of the Jebel Qara, forming structural escarpments. The massif underwent karstification and subsequent linear erosion. Today the Jebel is cut by a dendritic net of dry valleys, occasionally dammed by calcareous tufa dams. The transition between the southern escarpment of the Jebel and the plain below displays flat alluvial fans, bordered by a strip of beachrock, coastal dunes, and coastal lagoons, located in correspondence to estuaries. Dramatic soil erosion is evident, linked to intense human-triggered zoogeomorphological processes started in the Mid-Late Holocene after the introduction of pastoral land-use.